In vivo structure-function analysis of Drosophila Hairless. - Maier, D.; Marquart, J.; Thompson-Fontaine, A.; Beck, I.; Wurmbach, E.; Preiss, A. (Mechanisms of Development, 1997)
Hairless plays an important role as the major antagonist in the Notch signalling pathway in Drosophila. It appears to be a direct inhibitor of the signal transducer Su(H). Hairless encodes a pioneer protein which was dissected in a structure-function analysis; a series of deletion constructs was tested for wild type and gain of function activity in the fly as well as for Su(H) binding. Thereby, the Hairless protein was subdivided into the absolutely essential Su(H)-binding domain, similarly important N- and C-terminal domains and a central antimorphic domain. Therefore, Hairless protein might have additional functions apart from Su(H) binding and may antagonize Notch mediated cell-cell communication in a more complex way than currently anticipated.